Sports Brands Communication in the ‘COVID’ Age: Strategies, Representations, Identity and Consumption - Russo, Giovanna; Tallarita, Loredana (Italian Sociological Review, 2021)
The paper investigates the role of brand communication during the first period of pandemic age, in which Sport and PA were also called to redesign behaviours, cultural and consumer practices as well as to answer new questions of meaning. The new spirit of the time we are living in, is characterized by the domination of the medical-scientific language, and by a strong contraction of the economy in which trends and fashions appear scaled down and subordinate to new goals of well-being. The pandemic has increased the digitized experiences of sports practices, bringing out more and more aspects of individualism, narcissism, which are combined with a continuous search for well-being, health, beauty, fashion. Sports brands therefore appear as social spaces to observe the changes in sports communication and its consumption practices. The paper analysis how – during the first lockdown – the story-telling of sports brands has changed values, going to new socially responsible commitments in terms of global health and security. Following the multidimensional theory of communication, some emblematic cases of global sports brands are investigated through qualitative methods, in order to highlight the emergence of new issues: representations, identities, rules and consumption as innovative aspects of sports cultural production. The aim is to show sport and PA as a sort of pandemic “domestication” of the social reality we are experiencing.